Patient Profile Of Tinea Corporis In Dr. Soetomo General Hospital, Surabaya From 2014 To 2015 - Novita Oktaviana; Arthur Pohan Kawilarang; Damayanti - (Universitas Airlangga, 2018)
Background: The prevalence of dermatophytosis in Indonesia reach 52% of all fungal infections and is dominated by tinea corporis. Purpose: This study aimed to describe the clinical profile of tinea corporis patients in the Outpatient Unit of Dermatology and Venereology, Dr. Soetomo General Hospital, Surabaya. Methods: This study was a descriptive study with a case series method from patient medical records in the mycology division of the Outpatient Unit of Dermatology and Venereology, Dr. Soetomo General Hospital, Surabaya from January 1, 2014 to December 31, 2015 with 339 samples. Results: This study showed that tinea corporis patients were dominated by women counting for 113 patients in 2014 and 84 in 2015. Tinea corporal patients were dominated by the post-puberty age group between 40 and 50 years. Tinea cruris is the most common comorbid infection in this case. There were 85.25% of patients who showed positive results for hyphae structure, 72.57% of patients showed negative results for blastospore structure, and 64.31% of patients showed negative results for examination of Wood's lamp. There were 100 patients in 2014 and 86 patients in 2015 who received oral griseofulvin pharmacological therapy and 86.30% of these patients showed improvement in results after two weeks of treatment. Conclusion: Tinea corporis mostly attacks women and post-puberty age groups with tinea cruris as the most comorbid infections. The characteristic of tinea corporis could be shown as positive result for hyphae and negative for blastospore through the KOH test, and oral Griseofulvin is the most pharmacological therapy used for treatment